(untitled) (Zaporizhzhia Historical Review, 2021)
The article should be considered as continuation of the series of sketches devoted to the political biography of the outstanding personality of the Ukrainian liberation movement at the end of ХІХ century and at the beginning of ХХ century ñ Mykola Mikhnovskyi. The author explores the role and the place of Mykola Mikhnovskyi in forming the Ukrainian central council and civil political organizations in 1917 on the social and political background. The researcher also follows evolution of his political positions at the beginning of the Ukrainian revolution.